Length-weight relationship, condition factor, and age estimation of commercially important trawl species from Mersing coastal waters, Johor, Malaysia - Simon Kumar Das; Tou, Wee Xiang; Noorashikin Md Noor; Moumita De; Abdullah Samat (Penerbit Universiti Kebangsaan Malaysia, 2021)
Trawl fishing contributes to majority of the total fishes’ landings, supporting the choice of using age, growth determination, and condition factors (K) as part of the monitoring method for the fishes in Malaysia waters. This research specifically examines the use of age, length-weight relationship (LWR), and K to monitor the status of the commercially important fishes in Malaysia waters. LWR, K, and age of 10 commercially important trawl species (Gerres erythrourus, Drepane punctata, Otolithes ruber, Anodontostoma chacunda, Drepane longimana, Dendrophysa russelii, Sillago parvisquamis, Cynoglossus bilineatus, Sardinella brachysoma, and Alepes kleinii) from Mersing coastal waters, Johor, Malaysia, were studied. LWR (W=aLb ) indicated positive allometric growth (b > 3) for G. erythrourus and D. punctata but negative allometric growth (b < 3) for the other species. Results indicated that the species collected were in good conditions (average K, Kn > 1) in Mersing coastal waters, Johor, Malaysia. The daily growth rings of scale counts confirmed that the ages of the 10 species were typically less than 1 year (age range: 50-170 days; mean age: 95 days). The data obtained from this study will be useful for understanding the population growth pattern, age, and wellbeing of commercially important trawl species, which will facilitate better management techniques of these important fishery resources.